ASEDAS 2020 1st International Digital Art Exhibition - Mohamad Faizuan, Mat (ASEDAS 2020, 2020)
1st International Digital Art Exhibition organized by ASEAN Digital Art Society (ASEDAS). The ASEAN Digital Art Society or ASEDAS is an movement that brings together artists, artists and painters from ASEAN countries physically and virtually. The coalition was formed in April 2020 through an online discussion between its founder, Assoc. Prof. Ahamad Tarmizi Azizan (Atan Af) from Universiti Malaysia Kelantan (UMK), Malaysia, who is an academic and digital artist with Dr. Ariesa Pandanwangi from Universitas Kkristen Maharta, Indonesia, who is an academic and chairwoman of the 22nd Indonesian Community in the arts.